Association between exposure to greenness and atopic march in children and adults—A systematic review and meta-analysis - Wang, Xue; Zhou, Nan; Zhi, Yuxiang (Frontiers in Public Health, 2023)
Introduction Allergic diseases are a global public health problem. Food allergy, atopic dermatitis (AD), allergic rhinoconjunctivitis, allergic rhinitis (AR) and asthma represent the natural course of allergic diseases, also known as the “atopic march”. In recent years, a large number of studies have been published on the association between greenness exposure and allergic diseases. However, systematic reviews on the association between greenness exposure and multiple allergic diseases or atopic march are lacking. Methods In this study, PubMed, EMBASE, ISI Web of Science, and Scopus were systematically searched. Meta-analyses were performed if at least three studies reported risk estimates for the same outcome and exposure measures. Results Of 2355 records, 48 studies were included for qualitative review. Five birth cohort studies, five cross-sectional studies, and one case-control study were included for asthma meta-analysis, respectively. Four birth cohort studies were included for AR meta-analysis. Our results support that exposure to a greener environment at birth reduces the risk of asthma and AR in childhood. In addition, higher greenness exposure was associated with decreased odds of current asthma in children. Discussion There was a large heterogeneity among the included studies and most of them did not specify the vegetation type and causative allergens. Therefore the study results need to be further validated. In addition, a small number of studies evaluated the association between greenness and food allergy, AD and allergic rhinoconjunctivitis. More research is needed to strengthen our understanding of the association between greenness and allergic diseases.